Kemampuan Bacillus spp. Dalam Meningkatkan Ketahanan Tanaman Tomat Terhadap Infeksi Virus Keriting Kuning - Anshari, Ahmad; Aidawati, Noor; Salamiah, Salamiah (www.ulm.ac.id, 2025)
Tomato plants (L. esculentum Mill.) are vegetable crops. Tomato production in South Kalimantan is very low due to the attack of a plant disease, namely the yellow curly virus. Caused by the presence of the vector B. tabaci, control usually carried out by farmers is only controlling the vector with insecticides, not to control the virus. This control has negative impacts. Good control and has been widely used is biological control. Which utilizes microorganisms in tomato plants to induce resistance to yellow curly virus infection. In this study, a completely randomized design (CRD) was designed with one factor. The administration of Bacillus spp. derived from bamboo plant roots, elephant grass roots and chili roots was the factor tested. There were 5 treatments and 4 replications, The results of this study showed that the administration of Bacillus spp. derived from bamboo plant roots, elephant grass roots and chili roots, was able to induce tomato plant resistance to yellow curly virus infection. The lowest percentage of yellow curly virus attack intensity with an average (10.54%) was the tomato plants treated with Bacillus spp. derived from elephant grass roots. The average attack intensity of yellow curly virus on untreated and inoculated plants was 32.63%. The administration of Bacillus spp. from bamboo roots (T2), elephant grass roots (T3), and chili roots (T4) was shown to induce tomato plant resistance to yellow curly virus infection.